Impact of Bio-priming on Seed Quality Enhancement in Sweet Pepper - LAXMI DUNDAPPA CHOUGALA; PARASHIVMURTHY; RAME GOWDA; R SIDDARAJU; KN SRINIVASAPPA (Seed Research, 2026)
A laboratory study was undertaken to know the effect of biopriming on seeds with different biopriming agents like humic acid, vermiwash, compost tea, cytozyme seed+, VAM at the concentration of 30% on different vigour lots in sweet pepper at Department of Seed Science and Technology, University of Agricultural Sciences, Bengaluru. Among vigour level, high vigour seed lot was differed significantly with highest seed germination (86.0%), speed of germination (10.42), mean seedling length (8.52 cm), mean seedling dry weight (4.00 mg), seedling vigour index – I (730), seedling vigour index – II (342), total dehydrogenase activity (1.795), total soluble seed protein (72.98 µg/g), amylase activity (89.79 µmol/min) and decreased electrical conductivity of seed leachates (38.55 µS/cm) were recorded. Among the treatments biopriming with compost tea at 30% recorded significantly highest seed germination (84.0%), speed of germination (10.42), mean seedling length (8.65cm), mean seedling dry weight (4.00mg), seedling vigour index- I (726)seedling vigour index- II (338), total dehydrogenase activity (1.947), total soluble seed protein (74.36µg/g) and α-amylase activity (79.84µmol/min) and lowest electrical conductivity (34.39 µS/cm) over their control followed by vermiwash, humic acid, cytozyme seed+ and VAM at 30% each. Hence, from the results it was concluded that compost tea at 30% can be used to enhance seedling quality of the sweet pepper seeds.